Megaphone and Signpost: The Role of Netflix in the Internationalization of Korean Film and Television Productions - Yinger Wang; Juan-José Prieto-Gutiérrez (Communication & Society (Formerly Comunicación y Sociedad))
In recent years, several South Korean film and television productions have captured worldwide attention, notably exemplified by the 2019 film Parasite, which clinched the Academy Award for Best Picture as the first non-English-language work. Among them, the original Netflix series Squid Game stands out as a representative example, reaching No. 1 on Netflix’s Top 10 lists in 94 countries. The internationalization of these works has led to further enhancement of this country’s cultural diplomacy capabilities. As one of the creators of Squid Game, Netflix seems to impact this process. However, how much of a role it has played is still up for discussion. The principal objective of this article is to evaluate Netflix’s role in the internationalization of South Korean film and television productions, because on this basis, there will be a possibility to explore the potential replicability of this successful experience in other contexts and regions. Through a combination of quantitative and qualitative research methodologies, we investigated the development of its film and television industry since 1997. Our findings highlight Netflix’s role as a “megaphone” and a “signpost” for South Korean content on the global stage. Otherwise, it’s also necessary to recognize that the well-established and mature development of the Korean film and television industry itself is also an important reason for Netflix’s surprising success in South Korean content.